Measuring the Acceleration of Gravity Using a Smartphone, A4-Papers, and a Pencil - Aungtinee Kittiravechote; Thanida Sujarittham (International Journal of Advanced Science and Technology, 2020)
The measurement of the acceleration of gravity, g, is usually conducted in the science laboratory, especially in Physics subject. In contrast to the traditional method using a set of ticker timer, we propose a simple method to determine the magnitude of g using a smartphone, unused A4-sized papers, and a pencil. We use the smartphone application called Phyphox, operating in Timers and Acoustic Stopwatch mode to measure the time between two acoustic events. We then fold unused A4-papers together and put a pencil over them. After that, we flick the folded papers so that the pencil falls down. The first jingle from flicking causes the Acoustic Stopwatch to start whereas the second jingle from hitting of pencil on the floor makes it to stop. Through the measured time read by Acoustic Stopwatch and the height of folded papers, we are able to calculate the average of magnitude of the gravitational acceleration at the 5 different heights via (i) arithmetic mean, (ii) graphing by hand, and (iii) graphing by excel. Based on our observation of a free-falling object, we found that the magnitude of g at Bangkok equals to 9.760 m/s2. Comparison with the standard value of 9.783 m/s2 measured by the National Institute of Metrology (Thailand), our experimental value for gravity agrees well with the standard value which offers very good accuracy with a percentage of error of about 0.23%. We envisage that this work is not only economical, and can hence be conducted in places with limited access to laboratory tools, but also provides learning opportunities for students in hands-on practicing and data analysis.